2011
DOI: 10.1166/jnn.2011.5274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Morphology of Dispersed Nano-CeO2 on Far Infrared Emission Property of Natural Tourmaline

Abstract: Dispersed nano-CeO2 successfully grew on the surface of natural tourmaline powders by a precipitation method. The results of Fourier transform infrared spectroscopy (FTIR) showed that CeO2 (111) nanospots could apparently enhance the far infrared emission property of tourmaline in relation to CeO2 nanoparticles. This is the first report regarding the effect of the morphology of nano-CeO2 on the far infrared emission property of natural tourmaline. The results of the characterization by transmission electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…11 It is also known to enhance the far infrared properties of mineral compounds. 12,13 This study provides new insights into understanding and improving the dispersion of CeO 2 additive to impart thermal insulating properties to viscose fiber attributed to the infrared reflecting behavior of CeO 2 .…”
Section: Introductionmentioning
confidence: 88%
“…11 It is also known to enhance the far infrared properties of mineral compounds. 12,13 This study provides new insights into understanding and improving the dispersion of CeO 2 additive to impart thermal insulating properties to viscose fiber attributed to the infrared reflecting behavior of CeO 2 .…”
Section: Introductionmentioning
confidence: 88%
“…이러한 과정을 복사라고 하는데, 대부분의 금속의 복사율은 약 40 % 미만인 반 면에 세라믹의 경우 약 70 % 이상이다 [13,14]. 이러한 이유로 원적외선 방사 세라믹에 관한 많은 연구가 이루 어지고 있는데 [15], 맥반석, 토르말린, 금강석, 화산석, 적철석, 방해석 등은 원적외선을 방사한다고 알려진 광 물이며, 이는 원적외선 방사체 제조에 흔히 혼합되어 사 용되는 재료이다 [13][14][15][16][17]. 원적외선 방사 세라믹이란 가 열 시 3 µm 이상의 원적외선을 방출하는 물질을 일컫는 데, 이 세라믹 원료는 순도 및 조성의 편차를 보이게 되 어, 이에 대한 원적외선 방사 제품의 소결 조건의 최적 화가 필수적이다 [16].…”
Section: 서 론unclassified
“…Liang et al [14][15][16][17] have reported the performances and applications of some kinds of far infrared ceramics prepared by rare earth and minerals. It was found that appropriate content of rare earth could enhance the property of far infrared ceramics.…”
Section: Introductionmentioning
confidence: 99%